Measuring Sustainable Entrepreneurship and Eco-Innovation: A Methodological Proposal for the Global Entrepreneurship Monitor (Gem) - Saiz-Alvarez, J (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
After the UN’s adoption of 17 Sustainable Development Goals in 2015, it became clear that the relationship between sustainability and entrepreneurship was an area for re-examination. Traditional measures of entrepreneurial success rested largely on economic indicators; observatories like the Global Entrepreneurship Monitor (GEM) extended them, including cultural and social indicators. There is now a real need to measure and analyze the relationship between sustainable entrepreneurship and eco-innovation and drive positive economic activity outcomes, sustainable development, and social welfare. For GEM’s consideration, this paper proposes a reimagined tool by which to measure sustainable entrepreneurship and eco-innovation in businesses and assess their level of alignment with UN SDGs. Specifically, it presents a new measurement method, incorporating, but simplifying, a complex range of variables, which can be crystallized into a set of items (questions) to determine businesses’ commitment to entrepreneurship sustainability—social, economic, and environmental. The results can be cross-referenced with other relevant variables, and indicators proposed by the UN, to determine what causal or explanatory relationships might or might not exist. The proposal represents a valuable extension to existing data gathering tools, and will be of use to researchers and practitioners in the field of entrepreneurship—especially as its sustainability credentials and environmental impact are in the spotlight. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.